Tuberculosis in otolaryngological practice - Ghate, Girija A.; Chavan, Paresh S.; Thomas, James; Ingale, Mayur H. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Tuberculosis has become a common occurrence in Otorhinolaryngology with increasing number of extra pulmonary cases. Methods: This is a study of 27 patients who visited ENT OPD of Dr. D. Y. Patil Medical College, Pune, with variety of manifestations of tuberculosis in the ENT region. Results: Majority of those suffered from tuberculous cervical lymphadenopathy, other manifestations included laryngeal tuberculosis, tuberculous otitis media, lupus vulgaris and tuberculous infection of a pre auricular sinus. FNAC and histopathologic examination proved to be reliable tools of diagnosis. Five of these patients suffered from concurrent pulmonary tuberculosis. All these responded well to category 1 anti-tubercular therapy well. Conclusions: Tuberculosis in Otorhinolaryngology shows a variety of manifestations so it should be kept in mind whenever dealing with unusual presentations.